Enhanced antibacterial activity of ZnO-PMMA nanocomposites by selective plasma etching in atmospheric pressure - P. Dimitrakellis (Elsevier, 2021)
We present an alternative route to enhance antibacterial activity of polymer matrix nanocomposites that incorporate biocidal nanomaterials, using open-air atmospheric pressure plasma etching. We applied He/O2 discharges to rapidly remove the upper organic layers of ZnO -PMMA nanocomposite coatings, thus increasing the surface concentration of ZnO. To quantify the ZnO concentration from SEM images on the surface of the nanocomposite material, we developed and employed a new nanometrology method based on local variances of pixel luminosities and found a rapid increase of surface fraction up to 30% for the first 2 min of plasma treatment. Plasma etching resulted in enhanced antibacterial activity against Gram-negative E. coli cells after 4 h incubation under dynamic conditions. The results revealed an almost exponential drop of bacterial concentration with ZnO surface fraction, thus confirming the direct correlation of antibacterial activity with the interfacial area of the biocidal nanomaterial.